Adding Dimensions to the Analysis of the Quality of Health Information of Websites Returned by Google: Cluster Analysis Identifies Patterns of Websites According to their Classification and the Type of Intervention Described - Yaqub, Mubashar; Ghezzi, Pietro (Frontiers in Public Health, 2015)
Background and aims: Most of the instruments used to assess the quality of health information on the Web (e.g. the JAMA criteria) only analyze one dimension of information quality, trustworthiness. We try to compare these characteristics with the type of treatments the website describe, whether evidence-based medicine or note, and correlate this with the established criteria. Methods: We searched Google for “migraine cure” and analyzed the first 200 websites for: 1) JAMA criteria (authorship, attribution, disclosure, currency); 2) class of websites (commercial, health portals, professional, patient groups, no-profit); and 3) type of intervention described (approved drugs, alternative medicine, food, procedures, lifestyle, drugs still at the research stage). We used hierarchical cluster analysis to assess associations between classes of websites and types of intervention described. Subgroup analysis on the first 10 websites returned was performed. Results: Google returned health portals (44%), followed by commercial websites (31%) and journalism websites (11%). The type of intervention mentioned most often was alternative medicine (55%), followed by procedures (49%), lifestyle (42%), food (41%) and approved drugs (35%). Cluster analysis indicated that health portals are more likely to describe more than one type of treatment while commercial websites most often describe only one. The average JAMA score of commercial websites was significantly lower than for health portals or journalism websites, and this was mainly due to lack of information on the authors of the text and indication of the date the information was written. Looking at the first 10 websites from Google, commercial websites are under-represented and approved drugs over-represented. Conclusions: This approach allows the appraisal of the quality of health-related information on the Internet focusing on the type of therapies/prevention methods that are shown to the patient.